Ultrasound-assisted dispersive liquid-liquid microextraction for determination of enrofloxacin in surface waters - Dias, Reyla A. S. (2021)
This work describes the development of an HPLC-FLD methodology for the separation of five fluoroquinolones (ciprofloxacin, enrofloxacin, sarafloxacin, norfloxacin and levofloxacin) followed by optimization of the DLLME process for the clean-up and preconcentration of enrofloxacin in samples of seawater and river water. The mobile phase used for the chromatographic separation consisted of methanol: phosphate buffer (NaHPO4 H2O 0.04 M pH 3 with H3PO4 85 %), gradient eluted at a ratio of 20:80 (v:v). The mobile phase flow was maintained at 1.2 mL min-1. For the ultrasonic-assisted dispersive liquid liquid microextraction (UA-DLLME), the following conditions were used: 8 mL of sample with pH adjusted to 8, extraction solvent: 500 μL of chloroform, dispersive solvent: 500 μL of acetonitrile; samples were vortexed and sonicated for 2 minutes, each. The enrichment factor (EF) was 54.7 and the recovery was 70 %, achieving a limit of detection (LOD) of 0.11 μg L-1. Repeatability and intermediate reproducibility presented values of relative standard deviation (RSD) lower than 2 %. Finally, the optimized method was applied to the analysis of water and enrofloxacin was detected in both water samples with a concentration of 0.20 μg L-1 in the river and 0.12 μg L-1 in the seawater. However, recovery tests performed to evaluate the water matrices' effects on the extraction performance, presented recoveries of 72±6.1 for river water and 27±8.3 for seawater. These results demonstrate that hereby developed method is only suitable for water samples with a low salinity content.